The Way into Transcendental Philosophy from the Argument in Suhrawardī’s Philosophy of Illumination - Louchakova-Schwartz, Olga (Open theology, 2019)
This paper presents a phenomenological analysis of the argument in The First Discourse of Part 2 of Suhrawardī’s Philosophy of Illumination . Specifically, this argument is considered with regard to temporal extension of its logos, i.e., the succession of logical steps. Contrary to traditional views of Suhrawardī as a Neoplatonizing proponent of the primacy of essence over existence, the steps of his argument convey a much more nuanced picture in which ligh t emerges as the main metaphysical principle. First, Suhra wardī explicates full evidentiality in visible light (which is the most patent, ’ aẓhar, from the Arabic root ẓ- h-r = ‘to appear, be [made] manifest’): this light gives us the world as "this-there"; and second, as self-evidentiality ( ẓuhūru-hu , ‘being obvious to itself by itself’) in the first-person consciousness of the knower. Suhrawardī accesses these modes by reduction(s) which liberate the transcendental character of light. The correlation in the evidential mode of light between the knower and the objects serves as a ground for the claims of transcendental unity of the self and the world, and as a condition of possibility for knowledge. A juxtaposition of this approach with phenomenological philosophy suggests that in Suhrawardī’s analysis, the evidentiality of visual light plays a role of a new universal a priori. I show that under the phenomenological reduction, this a priori participates in constitution of ontological validities; and within the transcendental empiricism of the physics of light, this a priori underlies the construction of causality. Thereby, the Philosophy of Illumination suggests a new horizon of entry into transcendental phenomenological philosophy. The paper also contains a justification of a phenomenological reading of Suhrawardī’s work, including explanation of the historical reduction.